What is a clinically meaningful change in exhaled nitric oxide for children with asthma?. Issue 3 (7th January 2020) - Fielding, Shona; Pijnenburg, Marielle; de Jongste, Johan; Pike, Katherine; Roberts, Graham; Petsky, Helen; Chang, Anne B.; Fritsch, Maria; Frischer, Thomas; Szefler, Stanley; Gergen, Peter; Vermeulen, Françoise; et al.
Abstract: Introduction: Fractional exhaled nitric oxide (FE NO) may be a useful objective measurement to guide asthma treatment. What remains uncertain is what change in FE NO is clinically significant. Methods: An individual patient data analysis was performed using data from seven randomized clinical trials which used FE NO to guide asthma treatment. The absolute and percentage intra‐subject change in FE NO measurements over "stable" and also "unstable" 3‐month periods were described. Results: Data were available in 1112 randomized controlled trial participants and ≥1 stable period was present for 665 individuals. The interquartile range (IQR) and limits of agreement (LoA) for change in absolute FE NO among individuals whose initial FE NO was <50 parts per billion (ppb) were −7 to +9 ppb and −43 to +50 ppb, and for those with initial FE NO ≥50 ppb IQR was −29 to +17 ppb and LoA was −80 to +76 ppb. For percentage change in FE NO, the IQR and LoA for individuals whose initial FE NO was <50 ppb were −33% to +51% and −157% to +215%, and for those with initial FE NO ≥50 ppb were −33% to +35% and −159% to +192%. The variation in FE NO values for a stable period was similar irrespective of whether it was followed by a stable or unstable period. Conclusions: Over a 3‐month period where FE NO is initially <50 ppb, a rise of <10 ppb or of <50% (based on IQR) is unlikely to be related to asthma. When FE NO is initially ≥50 ppb an percentage change of <50% (based on IQR) is unlikely to be asthma‐related.